Strangely rhetorical : composing differently with novelty devices - Butts, Jimmy (Professor of writing) (Utah State University Press, 2023)
"Strangely Rhetorical establishes the groundwork for rhetorical strangeness as a lens under the broader interdisciplinary umbrella of rhetoric and composition and shares a series of rhetorical devices for practically thinking about how compositions are made unique. It explores how strange, novel, weird, and interesting texts work"--